A Decision-making Framework for Water Supply and Flood Protection Options in Net Present Value Terms - H J. J Boshoff; A J. Karrasch (The Australasian Institute of Mining and Metallurgy, 2016)
Mine planners frequently face the challenge of mitigating the impact of climatic events on mining operations, such as floods and droughts. Specific water management infrastructure can be implemented to meet operational requirements in response to these events. However, the effect of flood protection, for instance, may reduce the resilience of the site to drought. The probability and duration of unfavourable climate sequences significantly influences the net present value (NPV) of implementing specific water management infrastructure.Good life-of-mine planning will consider the incremental development of the project, and provide staged development plans. Water management infrastructure and the timing of implementation are facets of this process.CITATION:Boshoff, H J J and Karrasch, A J, 2016. A decision-making framework for water supply and flood protection options in net present value terms, in Proceedings Life-of-Mine 2016 Conference , pp 196–199 (The Australasian Institute of Mining and Metallurgy: Melbourne).